Assessment of the effectiveness of risk management processes used to develop a COVID-19 risk strategy at XYZ Public Health Care Facility - Thejane, Mosebi Alexis (University of the Free State, 2024)
This study's objective was to evaluate the effectiveness of the risk management procedures employed in the development of a COVID-19 risk management strategy at the XYZ public health care (PHC) facility in a YZ district in the Free State Province (FSP), South Africa. The findings and knowledge acquired from this study will be utilised to enhance the risk management procedures of the Department of Health and give other public health care facilities advice on how to create flexible and responsive risk management plans in the event that they encounter similar calamities in the future. The exploratory sequential design, a mixed methods research methodology that combines qualitative and quantitative research approaches, is used in this study. This hybrid research methodology was used to comprehend the effectiveness of the risk management processes implemented by the XYZ PHC facility in effectively addressing COVID-19 infections. To determine the elements of enterprise risk management and the crucial success factors for its effective implementation, a thorough literature review was carried out. Key references included established practices such as ISO 31000, COSO Integrated Enterprise Risk Management frameworks, Department of Health’s five-year strategic plan, annual performance plans, and other relevant literature materials. The XYZ PHC facility’s enterprise risk management processes were determined by examining the Department of Health’s Enterprise Risk Management Guideline and Framework. In this study, both research methods received equal priority (weighting). Qualitative method was used to provide a comprehensive understanding of the research question. The research question was fully understood through the application of the qualitative method by conducting in-depth interviews which extracted detailed information and contextual insights regarding the enterprise risk management processes utilised, which may not be available in the records and data but can be derived from the participants’ experiences, knowledge, and understanding of the COVID-19 pandemic crisis. The researcher utilised enterprise risk management's important critical success factors as a tool to inform the interview questions in order to enhance the depth and rigour of the conversations. Since risk management is a strategic function, face-to-face interviews targeted 20 senior and middle managers who were actively engaged in risk management activities and processes at the XYZ PHC facility. The outcomes of the first phase were then linked to the second phase by means of a questionnaire that was given to roughly 54 middle and upper managers based on the findings of the interviews. This helped with the interpretation of the qualitative findings. 𝗙𝗶𝗻𝗱𝗶𝗻𝗴𝘀: ERM process used to develop COVID-19 RM strategy in XYZ PHC facility was effective. In order to strengthen ERM processes, there is a need to cascades ERM to lower levels, use of quality improvement plan ‘s tools and interactive Information and Communication Technology and engage different stakeholders in the processes. Four critical success factors were identified for effective ERM implementation. 𝗖𝗼𝗻𝗰𝗹𝘂𝘀𝗶𝗼𝗻: Eight elements of ERM are present and functioning in the facility, while majority of top and middle staff have a fairly good ERM experience and are involved in ERM activities.
Dissertation(MBA (Business Administration))--University of the Free State, 2024
Keywords: Risk management (ERM); Enterprise Risk Management (ERM); Critical Success Factors (CSF); COVID-19; Organisational outcomes; Public health care; Productivity; ERM Effectiveness; ERM processes; Strategy planning (SP)